2020
DOI: 10.3390/v12040419
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number and Prevalence of Porcine Endogenous Retroviruses (PERVs) in German Wild Boars

Abstract: Porcine endogenous retroviruses (PERVs) are integrated in the genome of pigs and are transmitted like cellular genes from parents to the offspring. Whereas PERV-A and PERV-B are present in all pigs, PERV-C was found to be in many, but not all pigs. When PERV-C is present, recombination with PERV-A may happen and the PERV-A/C recombinants are characterized by a high replication rate. Until now, nothing has been known about the copy number of PERVs in wild boars and little is known about the prevalence of the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Fowler et al (2013) found a CNV region related to backfat thickness on chromosome 7 using a pig 60K Beadchip [10]. In the research of Revilla et 2020), CNVs were reported to be associated with fatty acid composition and growth traits, ear size, number of piglets born alive, and prevalence of porcine endogenous retroviruses [11][12][13][14]. In our previous research, CNVRs have reported associated with IMF content [15].…”
Section: Introductionmentioning
confidence: 81%
“…Fowler et al (2013) found a CNV region related to backfat thickness on chromosome 7 using a pig 60K Beadchip [10]. In the research of Revilla et 2020), CNVs were reported to be associated with fatty acid composition and growth traits, ear size, number of piglets born alive, and prevalence of porcine endogenous retroviruses [11][12][13][14]. In our previous research, CNVRs have reported associated with IMF content [15].…”
Section: Introductionmentioning
confidence: 81%
“…The copy number of PERVs in the genome of pigs; e.g., the number of integrated proviruses, differs depending on the pig strain, the age of the animals, the organ analyzed, and the method used for detection (for review, see [66]). The PERV copy number per cell in Göttingen and Aachen minipigs as measured by ddPCR varies around 50 and 70 [59,67]; the number PERV copies of German landrace pigs genetically modified to be used in xenotransplantation and wild boars are in the same range, from 50 to 70 [67,68]. These are the copy numbers of integrated proviruses when analyzing high-molecularweight DNA, not episomal DNA.…”
Section: Copy Numbermentioning
confidence: 99%
“…An extensive testing for PERV-A/C was not performed in other swine breeds than minipigs. In some cases, such a testing was performed and the results were negative: examples are wild boars [ 70 , 71 ] and Large White animals [ 71 ]. Further studies have been conducted in genetically modified animals generated for xenotransplantation purpose: PERV-A/C recombinants were only found in animals with a minipig proportion in their genome, e.g., in Large White/Duroc/Minipigs (15 out of 28 animals found positive) and in Large White/German Landrace/Duroc/Minipigs (three of five animals found positive) [ 71 ].…”
Section: Data On Perv-a/c Recombinants In Various Minipig Strainsmentioning
confidence: 99%